The AI Scalpel: Transforming Neurosurgical Procedures with Artificial Intelligence - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The field of neurosurgery, which demands the utmost precision and complex decision-making, is undergoing a profound transformation driven by the integration ...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning